Training planning in second language narrative writing. (22nd January 2020) - Khezrlou, Sima
Abstract: This study attempted to explore whether learners could be trained to use effective planning behaviours and whether this could affect their writing performance. A complete class of Iranian learners ( n = 42) of English as a foreign language received training in effective pre-task planning based on a number of operating principles. Writing performance, prior to and after the training, was measured through written narrative tasks. Retrospective interviews were also used to examine what learners did during planning. Results revealed that the effective planning behaviours are learnable, with many learners reporting positive ideas about the training programme. The findings also indicated significant improvements in learners' writing quality in terms of complexity, accuracy and fluency. Based on these collective findings, it is suggested that L2 learners need to be guided towards using more helpful planning behaviours, particularly those that are not forgotten with time.